RGS2 Modulation of Dopamine D2 Receptor Trafficking in Neuroblastoma Cells - Luessen, Deborah (Wake Forest University, 2015)
Dysregulated D2R expression and function is implicated in the pathophysiology of many diseases including Parkinson’s disease, schizophrenia, and drug addiction. D2R trafficking is vital to proper D2R function. While the expression and activity of D2Rs are altered in the pathology of these diseases, the underlying mechanisms of these changes remain unclear. As D2 receptors have a critical role in the pathophysiology of disease and serve as potential as a therapeutic target, the current study aimed to characterize the trafficking of D2R in a neuronal cell culture model. D2R internalization and recycling are critical for D2R function, including receptor desensitization and resensitization. Specifically, this study focused on the modulation of D2R trafficking by the regulator of G protein signaling, RGS2. Though RGS2 is most commonly associated with termination of GPCR signaling through accelerated GTPase activity, this study reveals a novel role of RGS2 knockdown in the modulation of quinpirole, a D2/D3 agonist, stimulated D2R internalization, recycling and β-arrestin translocation and distribution. This study provides evidence that RGS2 plays a vital role in modulation of D2R trafficking and could potentially serve as a target for manipulation of D2R activity in vivo.
Keywords: Dopamine; GPCR; Trafficking